Synthesis And Characterization Of La-Co/MgO Catalyst For Methane Dry Reforming - Cheng, C. K.; Chen, Loong Ong; Han, Jie Chan (2014)
In the present work, different loadings of lanthanum cobalt supported on magnesia catalysts were prepared for the methane dry reforming. XRD results showed that the peaks representing Co3O occurred at 2 = 37.0° and MgO or Co/MgO at 2 = 42.9°, 62.3°, 74.7° and 78.6°. As lanthanum loading increased, the crystallite size dropped from 24.5 to 17.9 nm. Reaction studies found that 5wt% La catalyst gave the highest formation of H24 and CO. However, the product composition was only about 1.6% (differential reactor). It was also found that the best formation rate was at CO2:CH feed ratio of 0.67.4